Surface and subsurface flow of a glacierised catchment in the cold-arid region of Ladakh, Trans-Himalaya - Soheb, Mohd; Bastian, Peter; Schmidt, Susanne; Singh, Shaktiman; Kaushik, Himanshu; Ramanathan, Alagappan; Nüsser, Marcus (Journal of hydrology, 2024)
Hydrological assessments of high-altitude catchments in Trans-Himalayan Ladakh are necessary for a better understanding of water availability in the context of irrigated cultivation under conditions of insufficient quantitative information on cryospheric meltwater discharge. In this study, an integrated spatially distributed temperature index model and a coupled surface/subsurface flow model were used to simulate daily, seasonal, and annual surface and subsurface flows to assess the proportion of corresponding source contributors from the Stok catchment. Snow and glacier meltwater discharge secures irrigated agriculture of more than 300 households in this catchment. The models were forced by temperature, precipitation, ice- and snow-covered areas at daily time steps with calibration (2019; 108 days) and validation (2018; 93 days) against the observed discharge. The simulated discharge shows a good agreement with the observed discharge with R2 and RMSE of 0.8 (p < 0.01) and 0.6 m3/s, respectively. The results between 2003 and 2019 show that the snowmelt contribution to the total annual discharge is largest with 65 %, followed by glacier melt and rainfall contributions of approximately 19 % and 16 %, respectively. A reduction in glacierised areas by 4.2 % was observed while snow-covered areas showed high inter-annual variation. Simulated subsurface flow makes up 62 % (mean = 37.2 × 106 m3) of the total discharge with less inter-annual variation. The simulation suggests that while surface flow ceases during the winter period and peaks in August, the annualized mean flow amounts to ∼23.7 × 106 m3. More than 50 % of the melt occurs in the summer months of June, July and August, when the intensity of snowmelt, ice melt, and rainfall reach its maximum. The findings of this study on meltwater availability and surface/subsurface flow is important for irrigated agriculture of Stok village on a local scale, and it might also help to better understand socio-hydrological dynamics and situations of water scarcity in the wider cold-arid region of Ladakh.